Detailing Architectural Design in Requirements Driven Software Development: The Tropos Case - Silva, Carla T. L. L.; Castro, Jaelson F. B.; Mylopoulos, John (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2003)
Software systems development happens within a context which organizational processes are well-established. Hence, software needs to be built with flexible architectures based in social and intentional concepts to enable software to evolve consistently with its operational environment, as well as, to accommodate new components and meet new requirements. This paper proposes to accommodate within UML-RT the concepts and features used for representing organizational architectures styles defined by the Tropos requirements driven development methodology. In doing so, it allows to provide a detailed representation of both the structure and behaviour of software architectural design using these styles. An ecommerce software system case study is used to illustrate the approach.